1992
DOI: 10.1111/j.1469-8749.1992.tb11517.x
|View full text |Cite
|
Sign up to set email alerts
|

Mobility Aids for Children With High‐level Myelomeningocele: Parapodium Versus Wheelchair

Abstract: SUMMARY The optimal method for providing mobility for children with myelomeningocele remains controversial. 39 children using a parapodium were compared with 29 children in wheelchairs. There were no significant differences between the two groups for medical complications, use of health‐care services or activities of daily living, although there were differences in the patterns of complications. Children using the parapodium were more likely to develop lesions of the lower extremities, to have dislocated hips,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
13
0
1

Year Published

1999
1999
2012
2012

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 38 publications
(15 citation statements)
references
References 25 publications
1
13
0
1
Order By: Relevance
“…The weight gain among older patients in this group agrees with an earlier study (36) but contradicts the suggestion that children either become obese and ''retreat to a wheelchair'' or become obese because they have given up walking (37,38). Patients in this least paralyzed group rarely ''retreat to wheelchairs'' (37)(38)(39)(40). The development of obesity is seen in the same level paralysis male group only after the age of graduation from high school and may be due to termination of team athletic activities and/or the adoption of a more sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…The weight gain among older patients in this group agrees with an earlier study (36) but contradicts the suggestion that children either become obese and ''retreat to a wheelchair'' or become obese because they have given up walking (37,38). Patients in this least paralyzed group rarely ''retreat to wheelchairs'' (37)(38)(39)(40). The development of obesity is seen in the same level paralysis male group only after the age of graduation from high school and may be due to termination of team athletic activities and/or the adoption of a more sedentary lifestyle.…”
Section: Discussionsupporting
confidence: 62%
“…The observations we report in this study, therefore, reflect a greater emphasis on weight control and may not be comparable with other groups of myelomeningocele patients, as suggested by Liptak et al (39).…”
Section: Discussionmentioning
confidence: 40%
“…Of those, there were none at evidence level I, nine at level II 1,2,3,4,5,6,7,8,9 , none at level III, 11 at level IV 10,11,12,13,14,15,16,17,18,19,20 , and none at level V. These studies appeared to imply that there is little benefit to walking with a parapodium, hip-knee-ankle-foot orthosis, or reciprocating gait orthosis. According to the studies, most children who walked with these orthotic devices eventually gave up walking as teenagers and chose a wheelchair for a more energyefficient means of locomotion.…”
Section: Resultsmentioning
confidence: 92%
“…In the first domain titled, 'incidence and riskof fracture,' the search provided 37 Finally, for the 'Prevention and nonpharmacological and pharmacological treatment of osteoporosis' review, we initiated our search by focusing on randomized, quasi-randomized, and non-randomized controlled trials and cohort and case-control studies. Because of the low number of studies identified, we considered case studies and case series.…”
Section: Resultsmentioning
confidence: 99%
“…Liptak et al analysed 39 children who used a parapodium and 29 children in wheelchairs with MMC in a comparative study and showed that early use of the parapodium did not protect against fractures. 37 The most ideal mobility device remains controversial. Weight bearing during ambulation should not be confused with passive weight bearing using a device, such as a standing frame.…”
Section: Prevention and Non-pharmacological And Pharmacological Treatmentioning
confidence: 99%